Analisis Sistem Rekrutmen dan Seleksi pada Female Daily Network - Rosmaniar Rosmaniar; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The recruitment and selection system are a vital component in the Human Resources Management of an organization in supporting the achievement of organizational goals. The aim of this research is to determine the recruitment and selection system implemented at the Female Daily Network which consists of the recruitment and selection process, recruitment and selection decision making procedures and how to measure the success of the recruitment system itself. This research uses descriptive qualitative methods, by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained through observation, interviews, and documentation, while secondary data was obtained through books, previous research, and articles relevant to this research. The data source in this research is interview transcripts obtained from a number of respondents called research informants. The informants from this research were four people, consisting of one head of the human resources division, two human resources staff and one new employee, IT staff. The research results show that the recruitment and selection process start from the human resources department posting vacancies and applicants sending CV until the head of HR makes a decision whether to accept them or not.